2020
DOI: 10.1111/sdi.12940
|View full text |Cite
|
Sign up to set email alerts
|

The reliability and success of peritoneal dialysis during the COVID‐19 pandemic

Abstract: We evaluated the symptoms, changes in laboratory findings during the novel coronavirus disease (COVID‐19) pandemic, and the effect of depression in patients with peritoneal dialysis (PD). This is an observational and cross‐sectional study. All patients were asked to fill the clinical assessment form and Beck depression and anxiety inventory. Also, the last two laboratory evaluations during this period were examined. A total of 123 patients performing PD were included. None of the patients were diagnosed with C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 24 publications
1
27
0
Order By: Relevance
“…To our knowledge, there are no previous studies evaluating and comparing concerns or anxiety among dialysis patients. However, in an observational study from Turkey, PD patients did not have any concerning‐level anxiety, which is concordant with our results of less concerned PD patients [18]. Although preventive strategies were applied properly in the dialysis facilities, more concerned HD patients considered changing the current dialysis modality due to the outbreak in our study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…To our knowledge, there are no previous studies evaluating and comparing concerns or anxiety among dialysis patients. However, in an observational study from Turkey, PD patients did not have any concerning‐level anxiety, which is concordant with our results of less concerned PD patients [18]. Although preventive strategies were applied properly in the dialysis facilities, more concerned HD patients considered changing the current dialysis modality due to the outbreak in our study.…”
Section: Discussionsupporting
confidence: 89%
“…They initiated PD in 64 patients and succeeded to monitor 946 PD patients during the pandemic by telemedicine utilization [20]. While success and reliability of PD was reported during the pandemic [18,20], by published and unpublished experiences dialysis initiation approaches seem to be changing [8]. In clinical practice with advantages and positive perspectives, we could guide patients for PD preference during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…As the COVID‐19 pandemic persists, the fear of transmission remains a prominent factor limiting engagement of CKD patients with the health care system 18,19 . Patients with chronic illness such as CKD have continued to avoid clinic visits or haemodialysis sessions due to this fear 18,20–22 . As such, an increase in the demand for home therapies, including peritoneal dialysis and telehealth consultations was observed 22–24 …”
Section: Discussionmentioning
confidence: 99%
“…One of the studies conducted with 1023 PD patients on the RPM program showed that patients’ treatment adherence was improved, the proportion of poorly controlled hypertension decreased and the peritonitis rate did not change significantly [ 12 ]. In another study, PD modalities were compared during the lockdown period [ 18 ]. The study results showed that CAPD, APD and RPM–APD had a similar effect on hypervolaemia, blood pressure control, residual renal function, hospitalization and peritonitis episodes.…”
Section: Coronavirus Disease 2019 Pandemicmentioning
confidence: 99%